Neo-Esktraktivisme Tambang Timah di Pulau Bangka - Nugraha, Agung; Purwanto, Semiarto A. (Indonesian Center for Religion and Society Studies (InTReSt), 2020)
Tin mining on Bangka Island was monopolized by large companies since the colonial period until twenty years ago. Furthermore, illegal tin miners or unconventional mines (tambang inkonvensional or TI) are the main actors in tin exploitation. We conducted research on the network of tin mining actors to explain the social relations, capital, and business of tin miners. Through the case study method, we observed and interviewed our informants during the March-October 2018 period. Within the neo-extractivism framework, we examined that TI players were connected to the mining business supported by global investment through a network of sub-collectors, collectors, and the smelting industry. This network serves to legalize the tin obtained by TI while ensuring the supply of industrial raw materials to support exports. We conclude that there has been a shift from production to distribution sectors. When emphasis on production processes, various institutional decays occur which involve state actors in it. Next, as attention is paid to the distribution chain, a shadow network that hides behind official companies emerges.